2017
DOI: 10.3389/fpsyg.2016.02077
|View full text |Cite
|
Sign up to set email alerts
|

What about False Insights? Deconstructing the Aha! Experience along Its Multiple Dimensions for Correct and Incorrect Solutions Separately

Abstract: The subjective Aha! experience that problem solvers often report when they find a solution has been taken as a marker for insight. If Aha! is closely linked to insightful solution processes, then theoretically, an Aha! should only be experienced when the correct solution is found. However, little work has explored whether the Aha! experience can also accompany incorrect solutions (“false insights”). Similarly, although the Aha! experience is not a unitary construct, little work has explored the different dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
224
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 140 publications
(277 citation statements)
references
References 48 publications
24
224
0
4
Order By: Relevance
“…The specific pattern revealed in the questionnaire analysis highlights the importance of assessing the individual dimensions of the multifaceted Aha! experience separately, as proposed by Danek and Wiley (), instead of obtaining only one global “Aha!” measure. Key dimensions of Aha!…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The specific pattern revealed in the questionnaire analysis highlights the importance of assessing the individual dimensions of the multifaceted Aha! experience separately, as proposed by Danek and Wiley (), instead of obtaining only one global “Aha!” measure. Key dimensions of Aha!…”
Section: Discussionmentioning
confidence: 99%
“…That the pattern for Surprise fitted the overall trend of lower ratings for chess players is in accordance with the findings of Webb et al (), although this dimension was previously reported not to be a good predictor of Aha! experiences (Danek & Wiley, ). Certainty, which in prior studies was always rated in alignment with the other dimensions (Danek & Wiley, ), showed the opposite pattern here.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations